2010
DOI: 10.1016/j.ejcts.2009.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of computerised tomographic angiography performed for preoperative evaluation before coronary artery bypass grafting

Abstract: Because preoperative CT angiography considerably affected management in one half of patients, we recommend its use as a routine test before CABG, unless contraindicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
2
23
1
Order By: Relevance
“…Agreement of chest X-ray and ultralow-dose with standard-dose CT regarding extent of thoracic atherosclerotic burden Stroke after cardiac surgery is a feared complication with still relatively high incidence 1 and recent studies have reported that pre-operative visualization of the thoracic aorta by CT may reduce stroke risk. 11 Several studies found a decrease in post-operative stroke rates from 3.0 to 0.7% 22 and from 9.0 to 0.4%, 23 respectively of patients undergoing pre-operative CT compared with a control group without pre-operative imaging. The investigators reported a change in surgical approach mainly with respect to different cannulation site selection and the use of an off-pump no-touch operation technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agreement of chest X-ray and ultralow-dose with standard-dose CT regarding extent of thoracic atherosclerotic burden Stroke after cardiac surgery is a feared complication with still relatively high incidence 1 and recent studies have reported that pre-operative visualization of the thoracic aorta by CT may reduce stroke risk. 11 Several studies found a decrease in post-operative stroke rates from 3.0 to 0.7% 22 and from 9.0 to 0.4%, 23 respectively of patients undergoing pre-operative CT compared with a control group without pre-operative imaging. The investigators reported a change in surgical approach mainly with respect to different cannulation site selection and the use of an off-pump no-touch operation technique.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators reported a change in surgical approach mainly with respect to different cannulation site selection and the use of an off-pump no-touch operation technique. 22,23 Currently, pre-operative CT is not routinely performed prior to cardiac surgery also owing to relatively high radiation exposure of CT with the potential risk of radiation-induced malignancy. Standard pre-operative work-up before cardiac surgery includes evaluation by chest X-ray, however, it was reported that plain X-ray only detects large calcified areas and generally underestimates thoracic aortic atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Park et al (2010) recommends preoperative CT angiography to be used as a routine test before CABG, unless contraindicated. More studies are needed to replicate this contention [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Preoperative 64-slice multidetector CT scan has been used in CABG patients to evaluate the incidence of pathologic lesions of the aorta and its major branches. The finding of significant atherosclerosis can offer the opportunity to modify risk assessment, CABG procedure itself, perioperative management or follow-up plan in about half of patients [ 56 ] . Surgical removal or endovascular isolation of the source of emboli could offer a definitive treatment option.…”
Section: Managementmentioning
confidence: 99%